The Relationship Between Father Absence and Intimate Partner Violence Victimization and Perpetration: Does Timing Matter? - Knox, Krysta N.; TenEyck, Michael F.; El Sayed, Sarah A. (Journal of developmental and life-course criminology, 2023)
Prior findings suggest that disruption of the family structure may serve as a risk factor for both offending and victimization late in life. Relatively few studies, however, have assessed the relationship of the timing of father absence during different developmental periods on intimate partner victimization and perpetration in adulthood. The current study addresses this gap in the literature by using a nationally representative longitudinal sample (Add Health) to examine the relationship between timing of biological father absence—in childhood and adolescence—and intimate partner violence victimization and perpetration in adulthood. Results indicate that having a father who was absent since birth is related to intimate partner offending in adulthood, controlling for lifetime measures of general criminal behavior and general victimization. However, there was no clear relationship between the timing of father absence on later intimate partner victimization or offending.